The Rhino Impact Investment Project—a new, outcomes-based finance mechanism for selected AfRSG-rated ‘Key’ black rhino populations - Glen Jeffries; Oliver Withers; Chris Barichievy; Chris Gordon (Pachyderm)
This article provides a detailed overview to date of the Rhino Impact Investment Project (RII). It shall explain in detail the overall objectives of RII—in principal, to develop the world’s first outcomes-based finance mechanism for a single species in order to overcome a variety of common problems seen in securing adequate funding for rhino conservation. A core part of RII relates to the rigorous selection process used to determine the sites to be included in the first iteration of this project, and this article focuses in detail on that process. Furthermore, the article shall examine the governance and management activity frameworks to be used for the RII, including the development of the African Rhino Theory of Change.